9.5.2 problem Example 3

Internal problem ID [1005]
Book : Differential equations and linear algebra, 4th ed., Edwards and Penney
Section : Section 7.6, Multiple Eigenvalue Solutions. Examples. Page 437
Problem number : Example 3
Date solved : Monday, January 27, 2025 at 03:22:52 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=x_{1} \left (t \right )-3 x_{2} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=3 x_{1} \left (t \right )+7 x_{2} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.017 (sec). Leaf size: 32

dsolve([diff(x__1(t),t)=1*x__1(t)-3*x__2(t),diff(x__2(t),t)=3*x__1(t)+7*x__2(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= {\mathrm e}^{4 t} \left (c_2 t +c_1 \right ) \\ x_{2} \left (t \right ) &= -\frac {{\mathrm e}^{4 t} \left (3 c_2 t +3 c_1 +c_2 \right )}{3} \\ \end{align*}

Solution by Mathematica

Time used: 0.002 (sec). Leaf size: 46

DSolve[{D[ x1[t],t]==1*x1[t]-3*x2[t],D[ x2[t],t]==3*x1[t]+7*x2[t]},{x1[t],x2[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to -e^{4 t} (c_1 (3 t-1)+3 c_2 t) \\ \text {x2}(t)\to e^{4 t} (3 (c_1+c_2) t+c_2) \\ \end{align*}